THE INFLUENCE OF LEADERSHIP AND MANAGEMENT COMPETENCE OF MADRASAH PRINCIPALS ON THE ENTREPRENEURIAL SPIRIT OF TEACHERS - Palah, Aap Nurul; Septialonna, Arip; Masitoh, Masitoh; Subasman, Iman (LP2M IAI Al-Khairat Pamekasan, 2025)
This study aims to analyze the effect of leadership and management competence of madrasah principals on the entrepreneurial spirit of teachers in MTs Kuningan Regency. The problem raised in this study is the low entrepreneurial spirit of teachers, which is allegedly closely related to leadership factors and management competencies that are not yet optimal. The novelty of this research lies in combining in-depth analysis of the relationship between educational leadership and managerial competence and its impact on entrepreneurship development in the context of Islamic education. Using qualitative methods, data were collected through in-depth interviews and document studies from various madrasahs in Kuningan Regency. The findings of this study show that the leadership of madrasah heads has a significant influence in shaping the entrepreneurial spirit of teachers, while management competencies have not had an adequate impact. The main conclusion of this study emphasizes the importance of improving the leadership capacity of madrasah principals in encouraging innovation and entrepreneurial spirit among teachers. The implication of this research is expected to be the basis of policy development and training for madrasah principals to strengthen the quality of leadership and management that is more adaptive to the needs of teachers in developing entrepreneurship.